Pemberdayaan Anggota Ekstrakulikuler Palang Merah Remaja (PMR) Dalam Pencegahan 3A (Anti Intoleransi, Anti Pelecehan Seksual, Anti Perundungan) di Lingkungan Sekolah dengan Metode Brainstroming : Di SMK Canda Bhirawa Pare - Siswoaribowo, Andika; Nurul Latifatul Anggraini; Aqilah, Muhammad Naufal; Febriani, Nurwanda Eka; Maharani, Putri Diah (STIKES dan AKZI Karya Husada Kediri, 2024)
Teenage development is often accompanied by several behavioral deviations that occur in adolescents, both in the home and school environment. These deviations include intolerance, sexual violence, bullying, and many more. This happens due to a lack of knowledge among today’s teenagers about the impacts of intolerance, sexual violence, and bullying, hence the need for efforts to impart understanding about anti-intolerance, anti-sexual violence, anti-bullying values to teenagers. One way this can be achieved is through the socialization and empowerment of Red Cross Youth (PMR) members in schools to broaden the horizons of teenagers and students can use the brainstorming method to discuss preventing acts of intolerance, sexual violence, and bullying to avoid behavioral deviations in school or outside. This community service uses a questionnaire distributed to 24 participants and employs a descriptive research method. The results obtained indicate that before the intervention, all PMR members (100%) had lesser abilities with a mean of 23.88, while after the intervention, all (100%) had good abilities with a mean of 44.17. This suggests that PMR members have experienced an increase in their knowledge scores about 3A prevention (Anti Intolerance, Anti Sexual Harassment, Anti Bullying). The Brainstorming can be more interactive, engaging, effective, and provide more understanding for respondents. It is recommended that 3A prevention be socialized to all respondents as a preventative measure against the occurrence of 3A.